LAYANAN BIMBINGAN KELOMPOK MELALUI PERMAINAN UNTUK MENINGKATKAN PERILAKU SOSIAL PESERTA DIDIK - Sabrina Dachmiati; Evi Fitriyanti; Cindy Marisa (Universitas Indraprasta PGRI, 2016)
In coaching to improve social behavior, certainly not out of the role of guidance and counseling activities in schools. Guidance and Counseling is an organization that provides assistance through special services and support activities provided to students with the aim to assist learners in the development of personal, social, learning and career. Of the many services that exist in guidance and counseling, one that can be used to improve the social behavior of learners is through group counseling services through the game. This research was conducted with the draft action research and development, while to analyze researchers used quantitative methods with experimental approaches. Based on the results obtained, we conclude that the group counseling services through the game can improve social behavior of learners, where changes in social behavior increases learners become better.Keywords : Guidance Group , Gaming , Social Behavior